Crystal structure, Raman spectra and microwave dielectric properties of Li2Mg3Ti1-x(Mg1/3Nb2/3)xO6 (0 ≤x ≤ 0.25) ceramics. Issue 10 (July 2018) - Yang, Y.K.; Pan, H.L.; Wu, H.T.
Abstract: Li2 Mg3 Ti1-X (Mg1/3 Nb2/3 )X O6 (0 ≤x ≤ 0.25) ceramics were prepared by a conventional solid-state reaction process. Their crystal structures, sintering characteristics, Raman spectra and microwave dielectric properties were then investigated. XRD patterns of the sintered samples indicated that all compositions showed a single phase and the rock-salt structure. As the (Mg1/3 Nb2/3 ) 4+ contents increase, the variations of ε r values showed a downward trend, which could be explained by the changes of polarizabilities and the shift of Raman vibration modes. Q·f values initially increased to a maximum value and then decreased with increasing of x values. In addition, τ f values decreased almost linearly with the x values, which significantly correlated with the thermal expansion coefficient. Excellent combined microwave dielectric properties with ε r = 14.79, Q·f = 204, 900 GHz and τ f = −18.43 ppm/°C were obtained for Li2 Mg3 Ti.95 (Mg1/3 Nb2/3 ).05 O6 ceramic sintered at 1550 °C.